2017
DOI: 10.1021/acs.jafc.7b01035
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Novel Vanillin Derivatives Incorporating a Bis(2-hydroxyethyl)dithhioacetal Moiety as Antiviral Agents

Abstract: A series of vanillin derivatives incorporating a bis(2-hydroxyethyl)dithioacetal moiety was designed and synthesized via a facile method. A plausible reaction pathway was proposed and verified by computational studies. Bioassay results demonstrated that target compounds possessed good to excellent activities against potato virus Y (PVY) and cucumber mosaic virus (CMV), of which, compound 6f incorporating a bis(2-hydroxyethyl)dithioacetal moiety, exhibited the best curative and protection activities against PVY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 42 publications
0
86
0
Order By: Relevance
“…Moreover, the activity of the title compound S8 is excess than those of the accordingly intermediates referring to the literature. 20 Bioassay results indicated that the introduction of naphthalene moiety to the dithioacetals can effectively improve the antiviral activity. In addition, among these compounds S1-S5, the R 2 groups affect the antiviral activity (S1, S5 > S2, S3, S4), with 1-naphthalene-methyl moiety at the para-position of dithioacetals in anti-TMV activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the activity of the title compound S8 is excess than those of the accordingly intermediates referring to the literature. 20 Bioassay results indicated that the introduction of naphthalene moiety to the dithioacetals can effectively improve the antiviral activity. In addition, among these compounds S1-S5, the R 2 groups affect the antiviral activity (S1, S5 > S2, S3, S4), with 1-naphthalene-methyl moiety at the para-position of dithioacetals in anti-TMV activity.…”
Section: Resultsmentioning
confidence: 99%
“…1) exerted markedly curative and protective activities against PVY and CMV. 20 Further research results by this group showed that dithioacetal C14 (Fig. 1) elicited excellent curative and protective activities against PVY, CMV and TMV.…”
Section: Introductionmentioning
confidence: 93%
“…It was cultured at 37 ℃, with a rotation speed of 200 r/min in a shaker cabinet for 7 Then, the fermentation broth was centrifuged at a rotation speed of 8000 r/min, the supernatant was ltered through a 0.22 µm millipore lter and stored at 4 ℃ for the preparation of crude extracts (Zhang et al 2017).…”
Section: Strains and Preparation Of Fermentation Brothmentioning
confidence: 99%
“…The species Potato virus Y (PVY) is the most important viral pathogen affecting potato crops and a serious threat to potato production worldwide (Davie et al 2017;Funke et al 2017). It can infect various crops, including potato, tobacco, tomato, pepper and other crops belonging to the Solanaceae family, and can cause serious damage and signi cant economic loss (Zhang et al 2017). Currently, few agents are available to effectively control this plant virus, such as ningnanmycin, dufulin, and ribavirin (Xiao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that natural products embody more “privileged structures” (DeSimone, Currie, Mitchell, Darrow, & Pippin, ) than purely synthetic chemical libraries and possess the characteristics and therapeutic effects of Chinese herbs (Breinbauer, Vetter, & Waldmann, ). Natural product‐based drug discovery research programs represent important avenues for drug development (Mann, ), including antiviral drugs (Si et al, ; Si et al, ; Lee et al, ; Ryu et al, ; Zhang et al, ). For example, rheum emodin (1,3,8‐trihydroxy‐6‐methylanthraquinone) is an active ingredient sourced from herbs belonging to the genera rheum , polygonum , rhamnus , and senna .…”
Section: Introductionmentioning
confidence: 99%